Development of a novel system for in-situ repair of aeroengine airfoil via pulsed laser ablation. (April 2020) - Cha, D.; Diaz, O.G.; Liao, Z.; Gilbert, D.; Axinte, D.; Kell, J.; Norton, A.; O'Key, M.; Osborne, M.R.; Main, D.
Highlights: Pulsed Laser ablation (PLA) has been used for performing repair of aeroengine components. Limited material-component damage, comparable to an equivalent mechanical process has been demonstrated using PLA. A prototype system has been designed and presented to allow in-situ micromachining using PLA as material removal method. Deployment of the prototype system for in-situ micro-machining has been demonstrated inside an aeroengine. Abstract: A novel system for performing in-situ micro-machining of aero-engines for repair applications is proposed in this paper. Using Pulsed Laser Ablation (PLA) as material removal technique, surface cracks caused by foreign objects colliding with airfoils are removed by performing a layer-by-layer micro-machining in the area surrounding the damaged zone. Compared to conventional repair performed by micro-grinding, our invasive PLA system demonstrates a similar level of performance, evaluated from the point of view of fatigue strength in the high cycle (>10 7 ) regime. The follow-up fractographic and metallurgical analysis, indicated that although some microstructural characteristics are different between the repair methods, the incurred surface damage is limited in magnitude to a thin surface layer (<30 μm) and the influence on fatigue life is comparable. In the last section, a novel prototype system is presented which allows performing the PLA repair in-situ by use of a miniaturized laser scanning head coupled with a flexible mechanical deployment arm. The system has been successfully tested inside a Roll-Royce Trent jet engine; effectively this proves the possibility of performing in-situ laser micro-machining inside complex mechanical systems such as aero-engines, without the need for complex/expensive disassembly.